The Effect of Independence, Professionalism, and Objectivity on Internal Audit Quality - Rifa Budi Prasanti Rifa; Sri Rahayu; Nunuk Supraptini (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
International-scale garment manufacturing companies face increasing pressure to maintain product quality, operational compliance, business process efficiency, and consistency in internal audit standards. The declining achievement of internal audit results in the company may indicate that internal audit quality needs to be strengthened through auditor-related factors. This study aims to analyze the influence of independence, professionalism, and objectivity on internal audit quality at GG International Manufacturing Co., Ltd. This research employs a quantitative approach with an explanatory research design. The population of this study consists of internal auditors and parties involved in the internal audit process at GG International Manufacturing Co., Ltd. The sampling technique used is purposive sampling, with a total sample of 45 respondents. Primary data were collected through questionnaires, while secondary data were obtained from company documents and supporting literature. The data were analyzed using Partial Least Square–Structural Equation Modeling with the assistance of SmartPLS. The results indicate that independence, professionalism, and objectivity play positive roles in improving internal audit quality. Objectivity emerges as the most prominent factor, as auditors who are able to maintain impartiality, fairness, and evidence-based judgment can produce audits that are more accurate, reliable, and beneficial for the company. This study implies the importance of strengthening auditor independence, enhancing professionalism, and maintaining objectivity in the implementation of internal audits so that the audit function can support operational control, compliance, and company competitiveness.